Research advances in mechanism of melanosomes transport and regulation in melanocytes - NING Jing, ZHANG Ru-zhi (Jichu yixue yu linchuang, 2022)
Melanosome (MS) is a special membrane organelle which synthesizes, stores and transports melanin in melanocytes (MC). The diversity of human skin color lies on the type, quantity, distribution and maturation of MS. The transport of MS in MC is the result of the interaction between three kinesins and two kinds of cytoskeletons, which are affected by many regulatory factors. A variety of pigmented diseases are strongly associated with MS transport malfunction. A deeper understanding of the mechanism for MS transport may improve the cognition of MS transport-related diseases and potentially provide a novel strategy for clinical treatment and pharmaceutical development.